A Methacrylic Anhydride Difunctional Precursor to Produce a Hydrolysis‐Sensitive Coating by Aerosol‐Assisted Atmospheric Plasma Process. Issue 8 (5th June 2014) - Mertz, Grégory; Fouquet, Thierry; Becker, Claude; Ziarelli, Fabio; Ruch, David
<x xml:space="preserve">Abstract</x> In this paper, we focused our attention on the elaboration of a hydrolyzable plasma‐polymer produced by aerosol‐assisted atmospheric pressure plasma process. A dielectric barrier discharge (DBD) was hence fed with a commercial methacrylic anhydride precursor – bearing an anhydride hydrolyzable function and two methacrylates groups aiming at producing a highly cross‐linked deposit – to produce thin coatings of plasma‐polymerized (pp) methacrylic anhydride. IR and NMR were performed to highlight the retention of the hydrolyzable group. After immersion in water, mass spectrometry analysis was conducted on the aqueous medium to characterize the end‐products and consequently confirm the occurrence of a hydrolytic degradation. A huge 80% thickness decrease was finally pointed out by nanoscratch measurements after 10 days.<inline-graphic xlink:href="ark:/27927/pgh11nffmtj" content-type="ppap201400050-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />